THE ROLE OF FAMILY PSYCHOLOGY IN FORMING MORAL AND MORAL IMMUNITY AGAINST INFORMATION ATTACKS. GENDER STEREOTYPES: IMPACT ON CHILDREN'S UPbringing and SOCIAL CONSCIOUSNESS (Universal International Scientific Journal, 2026)
This article analyzes the essence of information attacks in the context ofglobalization and digital transformation, as well as their psychological and social impact on theconsciousness of young people. The theoretical foundations of the concept of spiritual and moralimmunity are highlighted, and the role of family psychology in its formation is revealed. Inaddition, the influence of gender stereotypes on child upbringing, personality socialization, and theformation of social consciousness is examined through a comprehensive approach. During theresearch, issues such as media literacy, critical thinking, mechanisms of social control, andpedagogical cooperation are widely discussed, and practical suggestions and recommendations aredeveloped.
Keywords: information attacks; moral and ethical immunity; psychology